"Made in China": an emerging brand in the global arms market. Issue 2 (3rd April 2017) - Li, Ling; Matthews, Ron
ABSTRACT: Possession of a brand is a sine qua non for economic success, not least because it connotes trust in delivering the value promised. Although Western arms exporters offer branded systems whose sales are influenced by price, there is a plethora of other economic variables, such as offset requirements and life-cycle support. Entrants to the international arms market will struggle without such arms "packages." China's entry, however, goes beyond the traditional economic paradigm. A four-stage historical model offers the backdrop for identifying the drivers that have forged its market entry into 55 countries worldwide. The strategy initially focused on sales of rudimentary military equipment for political purposes, but recently it has begun to commercialize exports, repositioning them from a low- to a high-tech sales trajectory. A Sino "brand" is thus emerging, reflecting both competitiveness and diplomatic considerations, especially non-interference in client state domestic affairs.